Andean Medicine Perspectives - Van der Hoogte, Liesbeth (1984)
In November 1981, the Popular Natural Medicine Coordinating Team began its work as an initiative of some field health teams. These objectives were set: a. Develop a health system for the South Andean people based on modern medicine and traditional Andean medicine, available to everyone, both culturally and economically. b. Give a scientific basis to traditional Andean medicine. In this article we want to talk about the value of traditional medicine in general, almost always underestimated, and the perspectives of traditional Andean medicine.